PNRA. South-pole directory listing - Biagioni, Stefania; Carlesi, Carlo; Carpen?, Andrea; Ramorino, Chiara; Rossi, Lucio (1992)
In the following all DATA-SET descriptors (DSD) contained in the "South-Pole Directory" (vers. 1992) are listed. The "South-Pole Directory" was a joint project between ENEA and CNR. The IEI/CNR took care of the data digitalization and check and of the english translation (where necessary). The ARF/CNR and the Progetto Antartide/ENEA joined the IEI/CNR in defining the acronyms of the Sensor_Names and of the Source_Names, together with the short and long names for the Data_Centers. Finally, the ARF/CNR, together with the C.R.E. "Clementel"/ENEA, carried out the data-entry into the International Network Directory (IND) system, with the assistance of the European Space Agency in Frascati. Surely it is possible that some errors may be found in the Directory, even after the check done by the IEI/CNR. We hope to improve the Directory by eliminating discrepancies and errors in the coming year revison. Therefore, DSD-authors are kindly requested to notify them. Finally, we want to thank once more all the research units (U.O.) of the National Program far Antarctic Research (PNRA) for their contribution to the "South-Pole Directory".